Pengaruh Job Crafting Terhadap Work Engagement Pegawai Lapas Kelas III Rangkasbitung - Galang Yoga Tama, Natanael; Jarodi, Odi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
A correctional institution is a correctional technical implementation unit that has the duty and function to provide guidance to prisoners. That way, the correctional officers are required to have work engagement or work involvement in carrying out their duties, and one of the factors that can increase work engagement is job crafting. This study aims to determine the effect of job crafting on the work engagement of Class III Rangkasbitung Correctional Officers. This research method uses quantitative methods with a population sample of 63 officers, where the entire population is sampled. There are a total of 38 statement items that will be researched and distributed to all officers. Based on the results of the study, the regression results between the two variables were Y = 39.584 + 0.281X, and the results of hypothesis testing analysis through the determination test showed that the job crafting variable had an influence of 10.8% on the work engagement of Class III Rangkasbitung Prison Officers. Then, from the results of the t value of (5,045) > from the t table (2,000), which means Ho is rejected and Ha is accepted, the conclusion of this study is that there is a positive relationship between job crafting and work engagement among class III prison officers in Rangkasbitung.